Efficacy and safety of acupuncture for postpartum hypogalactia: protocol for a systematic review and meta-analysis. Issue 3 (9th March 2023) - Bao, Qiong-Nan; Zhou, Yuan-Fang; Yin, Zi-Han; Bi, Qiu; Zhao, Hong-Bin; Zhang, Zhen-Yong; Liang, Fan-Rong
Abstract : Introduction: Breast milk is recognised as the best natural food for neonates, but many women experience postpartum hypogalactia (PH). Randomised trials have found that acupuncture exert therapeutic effect on women with PH. However, systematic reviews on the efficacy and safety of acupuncture are still lacking; therefore, this systematic review aims to evaluate the efficacy and safety of acupuncture for PH. Methods and analysis: Six English databases (PubMed, Cochrane Library, EMBASE, EBSCO, Scopus, and Web of Science) and four Chinese databases (China National Knowledge Infrastructure, Wan-Fang, Chinese Biomedical Literature and Chinese Scientific Journal) will be systematically searched from their establishment to 1 September 2022. Randomised controlled trials of the efficacy of acupuncture for PH will be reviewed. The study selection, data extraction and research quality evaluation will be conducted independently by two reviewers. The primary outcome is the change in serum prolactin level from baseline to the end of treatment. Secondary results include milk secretion volume, total effectiveness rate, degree of mammary fullness, rate of exclusive breast feeding, and adverse events. A meta-analysis will be performed using RevMan V.5.4 statistical software. Otherwise, a descriptive analysis will be conducted. The risk of bias will be assessed using the revised Cochrane risk-of-bias tool. Ethics and dissemination: This systematic review protocol does not require ethical approval because it does not include private information/data of the participants. This article will be published in peer-reviewed journals. PROSPERO registration number: CRD42022351849.